Chloride threshold value and initial corrosion time of steel bars in concrete exposed to saline soil environments. (18th January 2021) - Yang, Deqiang; Yan, Changwang; Zhang, Ju; Liu, Shuguang; Li, Jie
Highlights: The EIS method used to determine the CTV and initial corrosion time of steel bar. The inhabited effect of sulfate and other ions on chloride diffusion was analyzed. Prediction model of initial corrosion time of steel bar in was established. Abstract: Saline soil is widely distributed in Western China. Its main components have the characteristics of high concentration and many kinds of ions, which pose a serious threat to the service life of reinforced concrete in this area. Therefore, it is of practical significance to determine the initial corrosion time and the chloride threshold value (CTV) of steel bars. In this research, the electrochemical impedance spectroscopy (EIS) method was used to determine the initial corrosion time and the CTV of steel bars immersed in saline soil simulation solutions, and the influence of sulfate and other ions on the initial corrosion time and the CTV of the steel bars was analyzed, as well as the influence mechanism. Based on Fick's second diffusion law, considering the time-dependencies of the chloride diffusion coefficient and the surface chloride content, a prediction model for the initial corrosion time of a steel bar in concrete was established. The results showed that compared with the solution containing only chloride and the solution containing low concentration of sulfate, the initial corrosion time of steel bars in saline soil simulation solution was significantly longer, and the CTV was lower. The sulfate had an obvious inhibited effect on the diffusion of chloride, the corrosion products of sulfate could fill the pores of concrete, affect the microstructure of the transition zone and concrete resistance, and caused the initial corrosion time of the steel bars to increase. other ions in the simulation solution also inhibited the diffusion of chloride, HCO3 − ion reduced the pH value of concrete pore solution and made the CTV of steel bars decrease. The prediction model established in this research was in good agreement with the actual situation, which can provide experimental evidence for the service life prediction of reinforced concrete structures in a saline soil environment. In order to prolong the initial corrosion time of the reinforced concrete in a saline soil simulation solution, in addition to increasing the thickness of the concrete protective layer, other anti-corrosion measures were also needed.